Artificial Mind System Kernel Memory Approach - Hoya, Tetsuya (Studies in Computational Intelligence, 2005)
This book is written from an engineer's perspective of the mind. "Artificial Mind System" exposes the reader to a broad spectrum of interesting areas in general brain science and mind-oriented studies. In this research monograph a picture of the holistic model of an artificial mind system and its behaviour is drawn, as concretely as possible, within a unified context, which could eventually lead to practical realisation in terms of hardware or software. With a view that "the mind is a system always evolving", ideas inspired by many branches of studies related to brain science are integrated within the text, i.e. artificial intelligence, cognitive science / psychology, connectionism, consciousness studies, general neuroscience, linguistics, pattern recognition / data clustering, robotics, and signal processing.